Optimization of Biaxial Tensile Specimen Shapes on Aerospace Composite with Large Deformation - Haowen Luo; Jiangtao Wang; Xueren Wang; Xiangyang Liu (Aerospace)
This study focuses on optimizing cruciform specimen configurations for the biaxial tensile testing of soft composite materials used in the aerospace industry under conditions of large deformation. A comprehensive evaluation system based on stress–strain uniformity and load transfer efficiency was established, and the stability of these metrics during the tensile process was analyzed. Using finite element simulation and multi-parameter analysis, the main parameter set affecting specimen performance was identified. The influence of different parameters on stress–strain uniformity and load transfer efficiency was investigated. Based on the optimization criteria, an optimized planar cross-shaped specimen configuration was developed. This configuration demonstrated excellent performance stability during deformation, with final stress uniformity error controlled to within 2.2%. The final strain uniformity error was maintained at 2.9%. The fluctuation range of load transfer efficiency did not exceed 1.5%. This study provides guidelines for designing specimens for large deformation testing of soft composite materials and can be used as a reference for future work on optimizing specimens.